The Heterogeneous of State and State Governance: Case of Indonesian Irregular Migrants in the Netherlands - Soraya, Yasmine (UI Scholars Hub, 2020)
The main issues of Indonesian migrant workers mostly lies on pre-departure phase, especially related to the issuance of travel document. They manipulate their data for passport application. From the bigger picture, this occurs because the high rate | of corruption within the immigration office. However, the immigration department is not solely responsible for this problem, but also with BNP2TKI (National Body for the Placement and Protection of Indonesian Overseas Wor- kers) and the Ministry of Manpower as they responsible for issuing regulations and procedures for migrant worker. Additionaly, the Department of Foreign affairs, which accommodates and oversees all Indonesian embassies and consulates abroad, also plays a role concerning the legal and political protection of Indonesian citizens. The embassy or consulate consist of officials from many departments (immigration department, department of education and cultural affairs, etc.), and they are not only responsible to the ambassador but also their departments in Indonesia. The lack of integrated legal understanding between these four departments and the imbalance of work between them could be the factors of the issues related to the rights of migrant workers. The heterogeneity of the state above and the state governance happens not only in Indonesia but also in the destination country, and migrant workers should deal with two systems of legal gover- nance which also experience transformations through time. This paper will discuss the impact of the heterogeneous state and state governance to Indonesian migrant workers in the Netherlands and how the migrants themselves navigate with these two systems.